2005
DOI: 10.1038/ncb1312
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of MLL by HMG-domain protein iBRAF promotes neural differentiation

Abstract: Differentiation of progenitor cells into post-mitotic neurons requires the engagement of mechanisms by which the repressive effects of the neuronal silencer, RE-1 silencing transcription factor (REST), can be overcome. Previously, we described a high-mobility group (HMG)-containing protein, BRAF35, which is a component of a co-repressor complex that is required for the repression of REST-responsive genes. Here, we show that the BRAF35 family member inhibitor of BRAF35 (iBRAF) activates REST-responsive genes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
86
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 19 publications
7
86
0
Order By: Relevance
“…As BRAF35, iBRAF contains an HMG domain in its amino terminus and a coiled-coil domain in the carboxyl-terminal half of the protein. In the mouse developing brain, Braf35 is predominantly expressed in immature neurons at the edges of the ventricles whereas iBraf is expressed in mature neurons, with the highest level being present in the outer cortex (13). Consistent with this expression pattern it has been shown that iBRAF improves neuronal differentiation of P19 cells.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…As BRAF35, iBRAF contains an HMG domain in its amino terminus and a coiled-coil domain in the carboxyl-terminal half of the protein. In the mouse developing brain, Braf35 is predominantly expressed in immature neurons at the edges of the ventricles whereas iBraf is expressed in mature neurons, with the highest level being present in the outer cortex (13). Consistent with this expression pattern it has been shown that iBRAF improves neuronal differentiation of P19 cells.…”
supporting
confidence: 57%
“…iBraf was described as an antagonist of Braf35 during neuronal differentiation, based on the fact that iBraf recruits the H3K4 methyltransferase MLL to neuronal specific genes (13). Now we show that iBraf can form homodimers and heterodimers with Braf35.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, the BRAF35 homologue, an inhibitor of BRAF35 (iBRAF), has been shown to activate REST/NRSFregulated genes through the modulation of histone methylation (Wynder et al 2005). Analysis of mouse embryonic carcinoma P19 cells undergoing neuronal differentiation revealed iBRAF accumulation at the promoter of neuron-specific genes coincident with the augmented expression of neuron-specific synapsin, recruitment of the H3K4 methyltransferase mixedlineage leukaemia (MLL) and enhanced trimethylation of H3K4.…”
Section: Histone Modification and Neural Differentiationmentioning
confidence: 99%